2013
DOI: 10.1177/1474515113507166
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives on the educational preparation of cardiac nurses

Abstract: Cardiac patients believe that the education of cardiac nurses should be driven by experiences in practice, nevertheless they want nurses to be equipped to deliver care that is underpinned by a strong knowledge base and skills combined with an ability to engage, educate and deliver high quality care that is both compassionate and individualised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…Cardiac patients believe that nurses need more solid ECG and arrhythmia training (24) , and the simulation could help undergraduate students acquire these skills. Some studies have found improvements in ECG knowledge after multimedia activities (2) , the use of Blackboard © , WebCT © or Moodle © environments, or the incorporation of self-learning (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac patients believe that nurses need more solid ECG and arrhythmia training (24) , and the simulation could help undergraduate students acquire these skills. Some studies have found improvements in ECG knowledge after multimedia activities (2) , the use of Blackboard © , WebCT © or Moodle © environments, or the incorporation of self-learning (25) .…”
Section: Discussionmentioning
confidence: 99%
“…While this study reports on the care and outcomes of patients in an acute hospital setting, it is highly likely that similar results will be found more widely. It is also recognized that patients value care provided by a nurse with a level of knowledge and skills sufficient to support compassionate care and provide them with a knowledge of their treatment that includes medication and potential side‐effects . In addition the responsibilities of nurses in many countries are increasing.…”
Section: Rationale For the Heart Failure Nurse Curriculummentioning
confidence: 99%
“…a level of knowledge and skills sufficient to support compassionate care and provide them with a knowledge of their treatment that includes medication and potential side-effects. 19 In addition the responsibilities of nurses in many countries are increasing. In some countries the nurse uptitrates prescribed medication.…”
Section: Rationale For the Heart Failure Nurse Curriculummentioning
confidence: 99%
“…Além das orientações sobre os fármacos, outras questões primordiais a serem abordados pelos enfermeiros durante a consulta incluem: fatores de risco para doença cardíaca, dieta, exercício físico, saúde sexual, estresse e mudanças de estilo de vida 12 . Para realizar tais orientações, é fundamental o profissional possuir uma compreensão abrangente das condições cardiovasculares, além de conhecimento para implementar medida efetivas 23 .…”
Section: Discussão Categoria 1: a Consulta De Enfermagemunclassified